Two new applications of tan(F(?)/2) -expansion method - Ugurlu, Yavuz; Inan, Ibrahim E.; Bulut, Hasan (Elsevier Gmbh, Urban & Fischer Verlag, 2017)
In this study, we consider the tan (F-(xi)/2)-expansion methodfor the traveling wave solutions of the potential KdV equation (pKdV)and the (3 + 1)-dimensional shallow water wave equation (SVVWE). We find some traveling wave solutions such as trigonometric function, hyperbolic function, exponential function solutions. Then, we showthe two and three dimensional surfaces for some traveling wave solutions obtained in this study by the Mathematica. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Potential KdV equation the (3+1)-dimensional shallow water wave equation; Tan(F(xi)/2)-expansion method; Traveling wave solutions